(untitled) (Annals of Medical Research, 2021)
Aim: In our study, the aim was to assess quality of life and associated factors among patients with Alzheimer disease (AD) and to collect data about reducing the disease load.Material and Methods: Our study was performed with 117 patients with possible AD diagnosis according to National Institute of Neurological and Communicative Disorders and Stroke-Alzheimer’s Disease and Related Disorders Association (NINCDS-ADRDA) diagnostic criteria and 102 healthy individuals. The Whoqol-Brief (WB) was used to assess quality of life of individuals in the AD and control groups, while the Quality of Life-Alzheimer’s Disease (QOL-AD) scale was also administered to patients with AD.Results: There were no significant differences between the AD and control groups in terms of sex and gender (p=0.952; 0.186). In the AD group, points obtained in all WB areas were found to be significantly low compared to the control group (p=0.000). With increasing disease stage, disease duration and patient age, the WB subareas and QOL-AD patient/family/weighted points were observed to display a statistically significant level of decrease (p=0.000). All WB areas and QOL-AD patient/family/weighted points for those who were illiterate, received care support and lived with children or relatives (apart from QOL-AD family) were found to be statistically significant low compared to those who were literate, had attended primary/middle and high school, lived on their own and did not receive care support (p>0.05).Conclusion: Our data show that the quality of life of patients with AD is low. The fall in quality of life appears to be parallel to increasing disease stage, disease duration, patient age and low educational level, living outside their own home and care support needs. Keywords: Alzheimer disease; quality of life; Whoqol-brief; quality of life-Alzheimer disease.